Evaluation of viral load in infants hospitalized with bronchiolitis caused by respiratory syncytial virus - Scagnolari, Carolina (Med Microbiol Immunol, 2012)
The relationship between viral load, disease severity and antiviral immune activation in infants suffering from respiratory syncytial virus (RSV)-associated bronchiolitis has not been well identified. The main objective of this study was to determine the existence of a correlation between RSV load and disease severity and also between different clinical markers and mRNA levels of the interferon stimulated gene (ISG)56 in infants hospitalized for bronchiolitis. We also evaluated whether viral load tended to be persistent over the course of the RSV infection. The levels of RSV-RNA were quantified in nasopharyngeal washings, collected from 132 infants infected with RSV as a single (90.15%) or as a dual infection with other respiratory viruses (9.85%). Results indicated that viral load was positively related to the clinical severity of bronchiolitis, the length of hospital stay, the levels of glycemia and the relative gene expression of ISG56, whereas an inverse correlation was observed with the levels of hemoglobin. We also found that the RSV load significantly decreased between the first and second nasopharingeal washings sample in most subjects. These results suggest that infants with high RSV load on hospital admission are more likely to have both more severe bronchiolitis and a higher airway activation of antiviral immune response.